1998
DOI: 10.2114/jpa.17.195
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Responses from Repeated Exposures to Severe Cold with Intermittent Warmer Temperatures.

Abstract: This study was conducted to evaluate physiological reaction and manual performance during exposure to warm (30 degrees C) and cool (10 degrees C) environments after exposure to very low temperatures (-25 degrees C). Furthermore, this experiment was conducted to study whether it is desirable to remove cold-protective jackets in warmer rooms after severe cold exposure. Eight male students remained in an extremely cold room for 20 min, after which they transferred into either the warm room or the cool room for 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The level of maximal blood pressure was reached 5 min after the starting of the cold exposure, and blood pressure stayed almost at the same level during the 15-min cold exposure. SBP and DBP responses in the present study were in accordance with previous studies (Ozaki et al 1998(Ozaki et al , 2001, which have been carried out with normotensive participants in warmer winter clothing (2.3 clo) under colder test conditions. SBP has been reported to increase from 118 to 126, 129, and 128.5 mmHg after the first, second and third 20-min exposure to -25°C with 20-min warm up in 30°C between two cold exposures (Ozaki et al 1998).…”
Section: Effect Of Repeated Cold Exposures On Thermophysiological Ressupporting
confidence: 92%
See 1 more Smart Citation
“…The level of maximal blood pressure was reached 5 min after the starting of the cold exposure, and blood pressure stayed almost at the same level during the 15-min cold exposure. SBP and DBP responses in the present study were in accordance with previous studies (Ozaki et al 1998(Ozaki et al , 2001, which have been carried out with normotensive participants in warmer winter clothing (2.3 clo) under colder test conditions. SBP has been reported to increase from 118 to 126, 129, and 128.5 mmHg after the first, second and third 20-min exposure to -25°C with 20-min warm up in 30°C between two cold exposures (Ozaki et al 1998).…”
Section: Effect Of Repeated Cold Exposures On Thermophysiological Ressupporting
confidence: 92%
“…Numerous studies have been conducted to demonstrate the effects of long-term exposure to cold (Leppaluoto et al 2001;Makinen et al 2006;Reynolds et al 2007). On the other hand, investigations of the effects of short-term repeated cold exposures on health and physiological responses are limited in number (Ozaki et al 1998(Ozaki et al , 2001Tochihara 2005;Kim et al 2007). However, these short cold exposures are very common in daily life during winter and have become more increasingly common in industry.…”
Section: Introductionmentioning
confidence: 99%
“…The rewarming of toes started only after 15-20 min of exercise. Other authors have also observed the later onset of the recovery of toe skin temperature 6) .…”
Section: Factors Affecting Foot Coolingmentioning
confidence: 76%
“…This effect can be related to slower warm-up of toes in footwear with a steel toe cap that has a higher thermal inertia (ca 100 g extra mass). After cold exposure the toe temperatures start to warm up after 5-15 min of a warm break or exercise 5,6,12,[26][27][28] .…”
Section: Mechanical Injuriesmentioning
confidence: 99%
“…Even exposure to less severe cold, which does not lower core temperature markedly, may produce cognitive (Palinkas, 2001; Mäkinen et al, 2006; Muller et al, 2012) and physical (Drinkwater and Behm, 2007) decrements, which may adversely affect performance and health (Tanaka et al, 1993; Palinkas, 2001). Brief periodic rewarming breaks throughout the day are recommended for restoring or preventing impairments in physiological and psychological performance for people exposed to the cold in occupational or leisure activities (Ceron et al, 1995; Ozaki et al, 1998; Brown et al, 2012). For example, in a protocol involving 3 sets of alternating 20-min exposure to −25°C in an industrial freezer with 20-min rewarming at 30°C or rest at 10°C, the protocol involving rewarming had a more positive effect than rest at 10°C on body temperature, hand tremor, counting task performance, and thermal and pain sensations.…”
Section: Introductionmentioning
confidence: 99%